Soft Switching of Three-Phase AC to DC CIHRC with Wireless Power Transfer (WPT) Function - Rahimi Baharom (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
This paper presents the verification of soft switching condition for three-phase AC to DC current injection hybrid resonant converter (CIHRC) with wireless power transfer (WPT) function. Details on the operation of current injection technique with the lossless zero voltage switching (ZVS) condition on shaping the high power factor of supply current waveforms are presented. With a suitable high switching frequency operation, the proposed resonant converter is capable to operate with ZVS conditions, thus, allowing reduction in the size of inductive and magnetic components. Selected results are also presented to verify the lossless ZVS condition for three-phase AC-DC CIHRC with WPT function.